Jahrbuch des Kunsthistorischen Museums Wien, Band 15/16 Quellen und Regesten zur Schatzkammer, Gemäldegalerie und zu den drei Kabinetten aus dem Archivbestand des k. k. Oberstkämmereramtes. 1777 bis 1787 mit einem Nachtrag zu den Jahren 1748 bis 1776 - Hassmann, Elisabeth (2015)
The Jahrbuch des Kunsthistorischen Museums Wien is among the oldest continuously published periodicals on art and art history issued by a museum. Volume 15/16 continues the basic research on primary sources representative of the periodical. It contains sources to the imperial collections of art and natural history from 1750 to 1800.